3, 4-Dihydroxyphenylacetic acid, a microbiota-derived metabolite of quercetin, attenuates acetaminophen (APAP)-induced liver injury through activation of Nrf-2. (2nd October 2016) - Xue, Huiting; Xie, Wenyan; Jiang, Zhihui; Wang, Meng; Wang, Jian; Zhao, Hongqiong; Zhang, Xiaoying
Abstract: 1. Acetaminophen (APAP) overdose leads to severe hepatotoxicity. 3, 4-dihydroxyphenylacetic acid (DOPAC) is a scarcely studied microbiota-derived metabolite of quercetin. The aim of this study was to determine the protective effect of DOPAC against APAP-induced liver injury. 2. Mice were treated intragastrically with DOPAC (10, 20 or 50 mg/kg) for 3 days before APAP (300 mg/kg) injection. APAP alone caused increase in serum aminotransferase levels and changes in hepatic histopathology. APAP also promoted oxidative stress by increasing lipid peroxidation and decreasing anti-oxidant enzyme activities. These events led to hepatocellular necrosis and reduced liver function. DOPAC increased nuclear factor erythroid 2-related factor 2 (Nrf-2) translocation to the nucleus and enhanced the expression of phase II enzymes and anti-oxidant enzymes, and thereby reduced APAP hepatotoxicity and enhanced anti-oxidant ability. 3. Our data provide evidence that DOPAC protected the liver against APAP-induced injury, which is involved in Nrf-2 activation, implying that DOPAC can be considered as a potential natural hepatoprotective agent.